Comparaciones de Variaciones de Densidad de Madera Medida Radiográficamente y Fluctuaciones de la Estructura Anatómica Dentro del Incremento Anual - Diaz-Vaz Olmedo, Juan Eduardo; Knigge, Wolfgang; Echols, Robert (Bosque (Valdivia), 1975)
Values of intra-incremental density and the dimentional variation of celles in Douglas Fir and Lodgepole pine are compared. The results show a great similarity between the two measurement compared in averaged sections every 0,24 mm on the radial direction. Small differences are noted and accounted for due to the accuracy that can be obtained by the X-ray method. Results obtained of the cellular dimentions in the annual ring and determinations of packing-density are compiled. In addition the influence of cell wall thicknen and cell diameter (Thickening and Flattening Effect) in the change of spring wood to summer wood is analized and discussed.